(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Analyze the current situation of distribution and structure of pharmacy human resources at district general hospitals in the Northern midlands and mountainous areas. Subjects and methods: Cross-sectional tissue research on 1425 pharmacy staff at 144 district-level public general hospitals working as of December 31, 2022 in the Northern midland and mountainous provinces. Results: Pharmacists with university degrees or higher account for a low proportion (15.3%), college and intermediate pharmacy degrees account for 50.6%, and pharmacists account for 0.28%. There is an imbalance in the structure of pharmaceutical human resources between urban and rural areas and even within a province. In most provinces in the Northern midlands and mountainous regions, the ratio of pharmacists/college and intermediate pharmacy, pharmacist/doctor, pharmacist/hospital bed are all low compared to regulations in Circular 03/2023/TT-BYT. The distribution of pharmacists working in district general hospitals is also unreasonable among provinces in the region, with an average of only 3.9 pharmacists/hospital. Conclusion: In the Northern midlands and mountainous areas, the proportion of pharmacists with university degrees or higher is low, mainly college and intermediate pharmacy degrees. There is still an imbalance in the pharmaceutical workforce structure between urban and rural areas. The ratio of pharmacists by bed, doctor and hospital is low.